Echocardiographic characteristics of PRKAG2 syndrome: a research using three-dimensional speckle tracking echocardiography compared with sarcomeric hypertrophic cardiomyopathy - Lu Tang; Xuejie Li; Nianwei Zhou; Yingying Jiang; Cuizhen Pan; Xianhong Shu (Cardiovascular Ultrasound, 2022)
Abstract Background PRKAG2 syndrome is a rare disease characterized as left ventricular hypertrophy (LVH), ventricular preexcitation syndrome, and sudden cardiac death. Its natural course, treatment, and prognosis were significantly different from sarcomeric hypertrophic cardiomyopathy (HCM). However, it is often clinically misdiagnosed as sarcomeric HCM. PRKAG2 patients tend to experience delayed treatment. The delay may lead to adverse outcomes. This study aimed to identify the echocardiographic parameters which can differentiate PRKAG2 syndrome from sarcomeric HCM. Methods Nine PRKAG2 patients with LVH, 41 HCM patients with sarcomere gene mutations, and 202 healthy volunteers were enrolled. Clinical characteristics, conventional echocardiography, and three-dimensional images were recorded, and reviewed by an attending cardiologist. We evaluated the parameters of left ventricular strains from three-dimensional speckle tracking echocardiography (3D STE) by TomTec software. Receiver operating characteristic (ROC) curves analysis was used to assess clinical and echocardiographic parameters’ differential diagnosis potential. Results The heart rate (HR) of the PRKAG2 group was significantly lower than both the healthy group (53.11 ± 10.14 vs. 69.22 ± 10.48 bpm, P < 0.001) and the sarcomeric HCM group (53.11 ± 10.14 vs. 67.23 ± 10.32 bpm, P = 0.001). The PRKAG2 group had similar interventricular septal thickness (IVS), posterior wall thickness (PWT), and maximum wall thickness (MWT) to the HCM group (P > 0.05). The absolute value of GLS in the PRKAG2 group was significantly higher than HCM patients (-18.92 ± 4.98 vs. -13.43 ± 4.30%, P = 0.004). SV calculated from EDV and ESV in PRKAG2 syndrome showed a higher value than sarcomeric HCM (61.83 ± 13.52 vs. 44.96 ± 17.53%, P = 0.020). The area under the ROC curve (AUC) for HR + GLS was 0.911 (0.803 -1). For HR + GLS, the sensitivity and specificity of the best cut-off value (0.114) were 69.0% and 100%, respectively. Conclusions PRKAG2 patients present deteriorated LV diastolic function and preserved LV systolic function. Bradycardia and preserved GLS are useful to identify PRKAG2 syndrome from sarcomeric HCM, which may be beneficial for clinical decision-making.